Attenuated lipopolysaccharide-induced inflammatory bladder hypersensitivity in mice deficient of transient receptor potential ankilin1. Issue 1 (December 2018) - Kamei, Jun; Aizawa, Naoki; Nakagawa, Takayuki; Kaneko, Shuji; Kume, Haruki; Homma, Yukio; Igawa, Yasuhiko
Abstract Transient receptor potential ankyrin 1 (TRPA1) channel expressed by urothelial cells and bladder sensory nerve fibers might act as a bladder mechanosensor and nociceptive transducer. To disclose the role of TRPA1 in bladder function and inflammation-associated hypersensitivity, we evaluatedin vitro andin vivo bladder function and inflammatory mechanosensory and nociceptive responses to intravesical lipopolysaccharide (LPS)-instillation in wild type (WT) and TRPA1-knock out (KO) mice. At baseline before treatment, no significant differences were observed in frequency volume variables, in vitro detrusor contractility, and cystometric parameters between the two groups in either sex. LPS-instillation significantly increased voiding frequency and decreased mean voided volume at 24–48 hours after instillation in WT but not in TRPA1-KO mice. LPS-instillation also significantly increased the number of pain-like behavior at 24 hours after instillation in WT mice, but not in TRPA1-KO mice. Cystometry 24 hours after LPS-instillation revealed shorter inter-contraction intervals in the WT mice compared with TRPA1-KO mice. In contrast, inflammatory cell infiltration in the bladder suburothelial layer was not significantly different between the two groups. These results indicate that TRPA1 channels are involved in bladder mechanosensory and nociceptive hypersensitivity accompanied with inflammation but not in physiological bladder function or development of bladder inflammation.